FINANCIAL LITERACY AND COPING STRATEGY CHOICES AMONG MSME IN BANYUMAS REGENCY - Priandhita Wibawanti; Wida Purwidianti; Nawalin Nazah; Alfato Yusnar Kharismasyah (COMPETITIVE, 2026)
The global market competition demands that Micro, Small, and Medium Enterprises in Banyumas Regency have effective coping strategies to survive in dynamic conditions. This study aims to examine the influence of financial distress, self-efficacy, leadership skills, and financial literacy on the selection of coping strategies. A total of 105 respondents were included, with the sample size determined using Slovin’s formula at a 10% error tolerance level. Data analysis was conducted through multinomial logistic regression, with coping strategies categorized into three main choices: cost efficiency, downsizing, and bank loans. The results of study indicate that among the four variables tested, only financial literacy has a positive effect on the selection of coping strategies. Financial literacy increases the possibility of entrepreneurs choosing cost efficiency by 1.150%, downsizing by 2.103,9%, and bank loans by 3.412,1%. These findings underscore the role of financial literacy as key factor in determining strategies to withstand the pressures of global competition. Thus, financial literacy becomes a new perspective in the process of selecting coping strategies, while also contributing to the development of literature on factors influencing the resilience of Micro, Small, and Medium Enterprises. This study also helps identify best practices in utilizing online media for product promotion, thereby enhancing the competitiveness of businesses in Banyumas Regency.